Increasing the Rural Special Education Teacher Pipeline Through Asynchronous Online Instruction: A Program Description of the Colorado Christian University Alternative Certification Program. (September 2019) - Lohmann, Marla J.; White, Bushrod; Johnson, Kathy A.
There is a documented shortage of special education teachers nationwide, and many rural school districts report hiring uncertified or temporary teachers to fill the open positions. To meet the needs of rural schools in our state, Colorado Christian University developed an asynchronous online alternative special education teacher certification program. Colorado Christian University's program includes 12 months of online coursework, as well as remote video supervision. This article provides a brief description of the program and preliminary data supporting its effectiveness in meeting the needs of rural Colorado schools.